PERBANDINGAN EFEKTIVITAS SENAM NIFAS DAN PIJAT OKSITOSIN TERHADAP INVOLUSI UTERI PADA IBU POST PARTUM - Andeka ' Lisni; Misrawati ' '; Gamya Tri Utami (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Uterine involution is a backward process of uterine to a normal position same as before pregnant after birth. The alternate intervention for getting uterine involution time became minimal are postpartum exercise and oxytocin  massage. The aim of this research was to identify comparative effectiveness of postpartum exercise and oxytocin massage on maternal postpartum uterine involution using quasy experiment with post test only design with two comparison treatment design. Sample of this study were 34 people which divided into 17 people as post partum exercise group and 17 people as a oxytocin massage group based on inclusions criteria using purposive sampling technique. Each group got maximal 9 days intervention for 10 minutes each day. This research measured by observation sheet. The univariate analysis was conducted to show frequency distribution and bivariate analysis was conducted by independent sample T-test. The statistic showed p value (0,002) < alpha (0,05) which means that there was differences between comparative effectiveness post partum exercise and oxytocin massage on maternal post partum uterine involution. Result shows that mean of uterine involution in post partum exercise group was more decrease within 142,373 hours, while in oxytocin massage group was 161,060 hours. This research was recommended post partum exercise to be applied in nursing intervention for getting uterine involution time became faster in maternal post partum. Keywords : Oxytocin massage, post partum, post partum exercise, uterine involution